Cerebral lateralization and cognition : evolutionary and developmental investigations of behavioral biases - Forrester, Gillian S.; Hopkins, William D.; Hudry, Kristelle; Lindell, Annukka (Progress in brain research, 2018)
Cerebral Lateralization and Cognition: Evolutionary and Developmental Investigations of Motor Biases, Volume 238, the latest release in the Progress in Brain Research series, discusses interdisciplinary research on the influence of cerebral lateralization on cognition within an evolutionary framework. Chapters of note in this release include Evolutionary Perspectives: Visual/Motor Biases and Cognition, Manual laterality and cognition through evolution: An archeological perspective, Laterality in insects, Motor asymmetries in fish, amphibians and reptiles, Visual biases and social cognition in animals, Mother and offspring lateralized social interaction across animal species, Manual bias, personality and cognition in common marmosets and other primates, and more.